2015
DOI: 10.3892/ol.2015.3107
|View full text |Cite
|
Sign up to set email alerts
|

Expression changes of cell-cell adhesion-related genes in colorectal tumors

Abstract: Abstract. Epithelial tissues achieve a highly organized structure due to cell-cell junction complexes. Carcinogenesis is accompanied by changes in cell interactions and tissue morphology, which appear in the early stages of benign tumors and progress along with invasive potential. The aim of the present study was to analyze the changes in expression levels of genes encoding intercellular junction proteins that have been previously identified to be differentially expressed in colorectal tumors compared with nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 44 publications
5
63
0
Order By: Relevance
“…Consistent with an oncogenic role, CDH11, promotes invasion of prostate cancer cells and metastasis to bone (5,20). CDH11 expression is upregulated in colorectal tumors (24). In oral squamous cell carcinoma, a previous immunohistochemical study showed that CDH11 is overexpressed but did not perform functional studies (25).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with an oncogenic role, CDH11, promotes invasion of prostate cancer cells and metastasis to bone (5,20). CDH11 expression is upregulated in colorectal tumors (24). In oral squamous cell carcinoma, a previous immunohistochemical study showed that CDH11 is overexpressed but did not perform functional studies (25).…”
Section: Discussionmentioning
confidence: 99%
“…Claudins have also been suggested to have an important role in carcinogenesis. Bujko et al . firstly demonstrated that the concomitant decrease of CLDN5 and CLDN15 levels were associated with CRC development.…”
Section: Discussionmentioning
confidence: 99%
“…Methylation of the RET promoter CpG island is associated with poor CRC prognosis [22]. Lower expression of the tight junction protein-encoding gene JAM2 has been observed in colon tumors compared with normal specimens [23]. In a mouse genome-wide association study, GSG1L regulates glutamate receptor activity and was among the genes associated with a chromosome 15 colorectal cancer genetic susceptibility locus [24].…”
Section: Discussionmentioning
confidence: 99%